XIV Modern Literature. (13th August 2019) - Levay, Matthew; Bratton, Francesca; Krzakowski, Caroline; Keese, Andrew; Corser, Sophie; Livingstone, Catriona; West, Mark; Cooper, Samuel; D'Monte, Rebecca; Rodríguez Martín, Gustavo A; Saunders, Graham; Baker, William; et al.
Abstract: This chapter has eight sections 1. General. 2 British Fiction Pre-1945; 3. British Fiction 1945 to the Present; 4. Pre-1950 Drama; 5. Post-1950 Drama; 6. British Poetry 1900–1950; 7. British Poetry Post-1950; 8. Irish Poetry. Section 1 is by Matthew Levay; section 2(a) is by Francesca Bratton; section 2(b) is by Caroline Krzakowski; section 2(c) is by Sophie Corser; section 2(d) is by Andrew Keese; section 2(e) is by Catriona Livingstone; section 3(a) is by Mark West; section 3(b) is by Samuel Cooper; section 4(a) is by Rebecca D'Monte; section 4(b) is by Gustavo A. Rodríguez Martín; section 5 is by Graham Saunders and William Baker; section 6(a) is by Noreen Masud; section 6(b) is by Matthew Creasy; section 7 is by Alex Alonso; section 8 is by Karl O'Hanlon.